FIKIH HUBUNGAN ANTARUMAT BERAGAMA DI INDONESIA: - Rumadi Rumadi (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
Interfaith relation in Indonesia remains unresolved thoroughly. Although outwardly it looks harmonious and calm, but behind it there is a ready-threatening waves. This paper argues that disharmony among religious followers in Indonesia, particularly between Muslims and Christians, has rooted in Islamic jurisprudence (fiqh) which stipulates the doctrines of interfaith relation. This specifically delves into some religious edicts (fatwas) on this particular phenomenon issued by three leading Islamic organizations, namely Nahdatul Ulema (NU), Muhammadiyah, and the Indonesian Council of Ulema (MUI). These fatwas are deemed to be part of religious narration that rests in intellectual discourse which more or less affects the observance of religious life in Indonesia.